Penentuan Cadangan Premi pada Asuransi Jiwa Berjangka Status Joint Life Menggunakan Metode Canadian - Fira Septiyani Ibrahim; Dewi Murni (Journal of Mathematics UNP, 2022)
The  Premium reserves is an obligation that must be owned by a life insurance company to provide compensation to the heirs in the event of a claim. The purpose in this research is to formulate a premium reserves formulation for term life insurance with joint life status. This research is a theoretical study that examines the calculation of the joint life status term life insurance premium reserves using the Canadian method which the 2019 Indonesian Mortality Table (TMI) and examples of case applications. The calculation of reserves begins by forming a joint mortality and commutation table for two insured persons, forming a formula for combined life annuity, single net premium, and annual net premium. Thus, in this study, the formulation of joint life insurance premium reserves using the Canadian method is obtained.